STEM-EDS quantitative analysis method for micro trace elements on high-temperature alloy interface

By combining STEM-EDS with transmission electron microscopy, the challenge of quantitative analysis of trace elements at the interface of high-temperature alloys has been solved, achieving quantitative accuracy and statistical representativeness at the nanoscale, and improving the reliability and repeatability of the analysis results.

CN121384997AActive Publication Date: 2026-01-23INST OF METAL RESEARCH - CHINESE ACAD OF SCI +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511938702.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-22
Publication Date
2026-01-23
Estimated Expiration
2045-12-22

AI Technical Summary

Technical Problem

Existing technologies are insufficient for accurate, reliable, and statistically significant quantitative analysis of trace elements at the interface of high-temperature alloys at the nanoscale, and the repeatability and comparability of the analysis results are poor.

Method used

By employing STEM-EDS combined with transmission electron microscopy, and by preparing transmission electron microscopy samples and controlling the thickness of thin regions to be less than 100 nm, optimizing instrument parameters and data acquisition processes, low-magnification statistical morphology and high-magnification classification acquisition are performed. Confidence intervals are calculated based on the normal distribution assumption to achieve quantitative analysis of multiple types of interfaces.

Benefits of technology

It achieves a balance between quantitative precision and statistical representativeness at the nanoscale, improves the reliability and repeatability of analytical results, and provides highly statistically representative quantitative results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121384997A_ABST
    Figure CN121384997A_ABST
Patent Text Reader

Abstract

The invention discloses a STEM-EDS quantitative analysis method for micro-trace elements on a high-temperature alloy interface, and belongs to the technical field of material micro-analysis. The method comprises the following steps: preparing a transmission electron microscope sample of which the thickness of a thin region is less than 100nm; adopting a field emission or spherical aberration correction transmission electron microscope to carry out STEM imaging under 200-300kV; the method comprises the following steps: firstly, counting different feature morphology interfaces and a quantity ratio thereof under 2000 *-3000 *, then respectively selecting a representative interface from each type of interfaces under 200k *-300k * to carry out EDS surface scanning for 20-30 minutes, and starting drift correction during the period; dividing the interface into a weak segregation interface and a strong segregation interface according to an EDS result; dividing data into quadrats, and counting to obtain an average value of element mass percentage contents of the two types of interfaces, 95% confidence level of the average value and a quantity ratio of the average value; and calculating the final content of the target element. According to the method, the problem that the nanoscale spatial resolution and quantitative statistical representativeness cannot be considered in the prior art is solved, and the accuracy and repeatability of an analysis result are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of material microanalysis, and particularly relates to a high-temperature alloy interface microtrace element STEM-EDS quantitative analysis method. BACKGROUND

[0002] High-temperature alloys are widely used in key hot-end components such as turbine blades and turbine discs of aero-engine due to their excellent high-temperature performance. Once these components fail, serious accidents may occur, so the safety and reliability of the material are crucial.

[0003] In addition to the main elements, high-temperature alloys usually contain a variety of trace and microtrace elements (such as B, C, P and rare earth elements, etc.), and the total content is usually less than 1wt%. Although these elements have very low content in bulk materials, they tend to segregate at interfaces such as grain boundaries and phase boundaries. Among them, beneficial elements (such as B and Zr) can strengthen the grain boundary and improve the creep life and fatigue performance of the alloy; while harmful elements (such as S and P) will weaken the grain boundary, leading to premature failure of the alloy during service. Therefore, accurately determining the real content, distribution and occurrence form of these microtrace elements at the interface is the key to understanding their action mechanism, optimizing alloy composition design and prolonging the service life of the component.

[0004] Currently, the techniques for element analysis mainly include classical chemical analysis method, atomic absorption spectrometry, inductively coupled plasma optical emission spectrometry (ICP-OES), inductively coupled plasma mass spectrometry (ICP-MS), and electron probe microanalysis (EPMA). However, these techniques have obvious limitations: the classical chemical analysis method needs to completely dissolve the sample, and can only provide the average content of the element in the bulk phase, and cannot reveal the segregation behavior of the element in the micro-regions (especially the nanoscale interface) such as grain boundaries and phase boundaries; and the EPMA is limited by the micron-level spatial resolution (usually >1 μm) and the relatively high element detection limit (about 0.01-0.1wt%), and it is difficult to effectively identify and accurately quantify the segregation of trace elements at the nanoscale interface.

[0005] Scanning transmission electron microscopy (STEM) combined with X-ray energy dispersive spectroscopy (EDS) technology has nanoscale or even atomic scale resolution, which provides a powerful tool for the study of interface segregation. However, in practice, there are still a series of challenges in using STEM-EDS to quantitatively analyze the interface (especially the trace elements in the bulk after enrichment at the interface): first, there is a lack of systematic and standardized sample preparation standards, which makes it difficult to ensure the representativeness of the analysis area and avoid the artifacts introduced by sample preparation; second, the instrument parameter settings and data acquisition processes have not been unified, which makes it difficult to directly compare the analysis results of different laboratories; finally, and most importantly, the traditional point analysis or small area analysis lacks statistical representativeness and cannot reflect the segregation differences of different types of interfaces, resulting in a large amount of accidental analysis results and poor repeatability.

[0006] Therefore, there is an urgent need in the art to establish an accurate, reliable and statistically meaningful quantitative analysis method for micro-trace elements at the interface of high-temperature alloys while maintaining the original microstructure of the material, in order to make up for the shortcomings of the prior art. SUMMARY

[0007] The purpose of the present application is to provide a STEM-EDS quantitative analysis method for micro-trace elements at the interface of high-temperature alloys.

[0008] In order to achieve the above-mentioned purpose, the present application provides the following technical solutions: 1. A STEM-EDS quantitative analysis method for micro-trace elements at the interface of high-temperature alloys, comprising the following steps: a) preparing a transmission electron microscope sample, and controlling the thin area thickness of the sample to be less than 100 nm; b) using a field emission transmission electron microscope or a transmission electron microscope equipped with a spherical aberration corrector to perform STEM imaging at an acceleration voltage of 200 kV-300 kV, adjusting the beam spot size to 5-7, making the optical path coaxial, and optimizing the collection angle, energy resolution and detection efficiency of the EDS probe to make the EDS meet the detection accuracy requirements of micro-trace element analysis; c) using a low magnification of 2000 -3000 , statistically analyzing interfaces with different characteristic morphologies, and recording the proportion of the number of each type of interface, wherein when the normal direction of the interface along the length direction is Δθ≥10°, it can be marked as a curved interface; otherwise, it is marked as a straight interface; then under a high magnification of 200k -300k , a representative interface is selected in each type of interface for EDS area scanning data acquisition for 20-30 minutes; during the acquisition process, the electron beam drift correction function is enabled, and the probe current is controlled to be ≤0.0040 nA and the count rate is ≥1 kcps; d) According to the EDS data obtained in step c), the interface with element content between 0-0.1wt% and not containing 0.1wt% is defined as weak segregation interface, and the interface with element mass percentage content between 0.1%-1% is defined as strong segregation interface; e) The EDS data results of each type of interface collected in step c) are respectively divided into n*n quadrats, and n quadrats containing interfaces are selected to obtain the element mass percentage content a1, a2…a n of weak segregation interface and the element mass percentage content b1, b2…b n of strong segregation interface, respectively; f) The obtained element content data is averaged to obtain the average mass percentage content of elements of strong segregation interface and weak segregation interface, respectively: ; ; wherein, is the element mass percentage content at the i-th weak segregation interface; is the element mass percentage content at the i-th strong segregation interface; n is the number of quadrats; is the average mass percentage content of elements of weak segregation interface; is the average mass percentage content of elements of strong segregation interface; The obtained element content data is statistically analyzed, and the sample standard deviation is calculated to represent the dispersion degree: ; ; wherein, is the sample standard deviation of the element mass percentage content of weak segregation interface, is the sample standard deviation of the element mass percentage content of strong segregation interface; The A-type standard uncertainty of element content at the interface is estimated by the mean standard error: ; ; wherein, is the standard error of the average value of the element mass percentage content of weak segregation interface; is the standard error of the average value of the element mass percentage content of strong segregation interface; According to the selected 95% confidence level, the critical value of the distribution with degree of freedom is found to be , and the expanded uncertainty of the average value of element content of strong segregation interface and weak segregation interface is calculated: ; ; wherein, and represents the expanded uncertainty of the mean value at the 95% confidence level, which is the half-width of the confidence interval; The average value of the element in the weakly segregated interface element mass fraction and its 95% confidence level are: ; The average value of the element in the strongly segregated interface element mass fraction and its 95% confidence level are: ; g) Calculate the final mass percentage of the target element using the formula ; ; Wherein, x is the proportion of weakly segregated interfaces; y is the proportion of strongly segregated interfaces.

[0009] Further, in step a), an electrolytic polishing or focused ion beam method is used to prepare a transmission electron microscope sample, and the thickness of the thin area of the sample is controlled in the range of 50nm to 100nm.

[0010] Further, in step c), according to the interface feature morphology, identify and mark as straight line interface or curved line interface.

[0011] Further, in step b), the acceleration voltage of the transmission electron microscope is set to 200kV.

[0012] Further, in step c), the high magnification is 250k .

[0013] Further, in step c), the EDS area scan data acquisition time is 25 to 30 minutes.

[0014] Further, after step g), it further includes step h): comparing the calculated target element mass percentage content interval wt% with the known chemical composition mass percentage content wt0% of the element in the high-temperature alloy, when wt0% is located in the uncertainty interval of wt%, confirming that the detection result wt% has reliability.

[0015] Compared with the prior art, the high-temperature alloy interface micro-quantitative element analysis method based on STEM-EDS provided by the present application has the following significant technical effects: 1. The application realizes the unity of quantitative accuracy and statistical representativeness at nanoscale: through the systematic analysis process of "low-magnification statistical morphology-high-magnification classification collection-confidence interval calculation based on normal distribution", the traditional composition analysis limited to single point or small area is expanded to the statistical level of multi-type interface. Specifically, first, the interfaces of different morphological characteristics are statistically analyzed in a large range in the low-magnification STEM image to determine the proportion of weak and strong segregation interfaces, then the EDS signal collection of the two types of representative interfaces is carried out for a long time and high stability to improve the signal-to-noise ratio and accuracy of element quantification, and finally, based on the normal distribution assumption of multiple measurement data, the confidence interval of element content and the reliability of quantitative results are calculated at a specified confidence level. This innovative process design effectively overcomes the randomness and limitations of single area analysis, while maintaining the high spatial resolution of STEM-EDS sub-nanometer, it obtains quantitative results that can reflect the local chemical state and have high statistical representativeness, providing a new paradigm for reliable characterization of nanoscale interface composition.

[0016] 2. The application establishes standardized operation specifications, significantly improving the repeatability of the method and the reliability of the results: the key operation steps and instrument parameters are specified. Specifically, the sample thin area thickness is strictly controlled at 50-100 nm, effectively reducing the multiple scattering of the electron beam, providing a basic guarantee for quantitative accuracy; the acceleration voltage, beam spot size, probe current, count rate and collection time of up to 20-30 minutes are specified and drift correction is enabled, ensuring the high stability and high signal-to-noise ratio of the data collection process, creating conditions for accurate detection of micro trace elements. These specific parameters and steps together form a clear and operable standardized scheme, greatly reducing the result fluctuations caused by operational differences, making the analysis results of different times, different operators and even different laboratories have good comparability and repeatability.

[0017] 3. The application introduces an objective result verification mechanism to ensure the accuracy of the final data: after completing the element content calculation, an additional step of comparison verification with the nominal chemical composition of the alloy (or known overall composition) is added, by judging whether the measured value falls within its 95% confidence interval, to evaluate the reliability of the analysis results. This built-in quality control link provides an objective, quantitative and criterion-based data validity standard, significantly improving the credibility of the method output results, thereby providing more reliable basic data support for key applications such as composition design, interface regulation and service life prediction of high-temperature alloys. BRIEF DESCRIPTION OF DRAWINGS

[0018] Figure 1 High-magnification crystal boundary morphology and EDS area distribution map, wherein the box in (a) represents the target plot actually used to calculate the average value of element content, and (b) represents the EDS area distribution result of P element. Detailed Implementation

[0019] The preparation method of the present invention will be described in detail below with reference to the accompanying drawings. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.

[0020] Example 1 (1) Sample preparation A certain type of nickel-based superalloy material was used, and transmission electron microscopy (TEM) samples were prepared by electrolytic polishing according to the requirements of GB / T18907-2013 standard. A 10% (v / v) perchloric acid-acetic acid solution was used as the electrolyte, and double-jet thinning was performed at -20℃ and 30V. Calibration with a thickness standard confirmed that the thickness of the thin region of the sample was controlled at 70 nm, which meets the 50 nm-100 nm range requirement of this invention.

[0021] (2) Instrument preparation The tests were conducted using a FEIThemisZ field emission transmission electron microscope. The accelerating voltage is set to 200kV; The condenser beam spot size was adjusted to 7; Perform precise optical path alignment to ensure electron beam collimation; Optimize the EDS probe collection angle to ensure that the detector solid angle is greater than 0.7 srad.

[0022] (3) Content detection First in 2000 Under the conditions described, the thin area of ​​the sample was observed using a high-angle annular dark-field imaging system. Three interfaces with clear contrast were obtained, including one curved interface and two straight interfaces, with a ratio of 1:2.

[0023] Subsequently, a representative interface was selected from each type of interface and analyzed in 250k... The following 25 minutes of EDS surface scan data acquisition will be performed: Enable real-time drift correction function and use image feature tracking algorithm to automatically correct beam spot position; Control the probe current to 0.0040 nA; The count rate remained stable at 2389 cps; The acquisition area is 80nm×80nm in size.

[0024] Quantitative analysis of the collected EDS data (using the standard-free method) showed that the P element content of the linear interface was 0.12%, which was classified as a strong segregation interface.

[0025] One curved interface has a P element content of 0.08%, which is classified as a weak segregation interface.

[0026] (4) Data processing and error analysis The EDS data of the two interfaces is divided into a 10x10 quadrat grid, that is, each interface data contains 100 pixel points, from which 10 quadrats containing interfaces are extracted as statistical samples (n=10), and the EDS analysis software is used to obtain: Weak segregation interface P element mass percentage (wt%): 0.07, 0.09, 0.05, 0.06, 0.09, 0.10, 0.07, 0.09, 0.09, 0.08; Calculate the average value of the mass percentage of the element (wt%): ; Calculate the standard deviation of the sample (representing the degree of data dispersion) (wt%): ; Calculate the standard error of the average value of the mass percentage of the element of the weak segregation interface (wt%): ; Calculate the expanded uncertainty of the mean value at the 95% confidence level (i.e. half the width of the confidence interval): ; The average value of the mass percentage of the element of the final weak segregation interface and its 95% confidence level: ; Strong segregation interface P element content (wt%): 0.13, 0.14, 0.17, 0.15, 0.18, 0.11, 0.10, 0.19, 0.09, 0.10; Calculate the average value of the mass percentage of the element (wt%): ; Calculate the standard deviation of the sample (representing the degree of data dispersion): ; Calculate the standard error of the average value of the mass percentage of the element of the strong segregation interface (wt%): ; Calculate the expanded uncertainty of the mean value at the 95% level (i.e. half the width of the confidence interval): ; The average value of the mass percentage of the element of the final strong segregation interface and its 95% confidence level: ; The proportion of the number of weak segregation interfaces is x=1 / 3≈33.3%; The proportion of the number of strong segregation interfaces is y=2 / 3≈66.7%; The final mass percentage of P element (wt%) calculated by the formula of the application: ; The result is compared with the P element overall content of the alloy 0.12wt% measured by inductively coupled plasma mass spectrometry (ICP-MS), and the result is confirmed to be consistent with the chemical composition 0.12wt%. According to the judgment standard of the application, it is confirmed that the detection result wt% has reliability. High-magnification grain boundary morphology and EDS area distribution map are shown in Figure 1 Wherein, the block in (a) represents the target sample used for calculating the average value of the element content, and (b) represents the EDS area distribution result of the P element.

[0027] Example 2 (1) Sample preparation A certain type of nickel-based superalloy material is taken, and a transmission electron microscope sample is prepared according to the requirements of GB / T18907-2013 standard by using electrolytic polishing method. 10% volume fraction perchloric acid-acetic acid solution is used as electrolyte, and double-spray thinning is carried out at-20℃ and 30V voltage. Through thickness standard calibration confirmation, the sample thin area thickness is controlled in 68nm, which meets the range requirements of 50nm-100nm of the application.

[0028] (2) Instrument preparation FEI Themis Z field emission transmission electron microscope is used for testing: the acceleration voltage is set to 200kV; the condenser beam spot size is adjusted to 7; fine light path is aligned to ensure the collimation of the electron beam; the collection angle of the EDS probe is optimized to ensure that the detector solid angle is greater than 0.7srad.

[0029] (3) Content detection Firstly, the sample thin area is observed by using high-angle annular dark-field image system at 2000 kV, and 6 interfaces with clear contrast are obtained by statistics, including 2 curved interfaces and 4 straight interfaces, and the number ratio is 1:2. Subsequently, a representative interface in each type of interface is selected to perform 25-minute EDS area scanning data acquisition at 250k V: the real-time drift correction function is enabled, the image feature tracking algorithm is used to automatically correct the beam spot position; the probe current is controlled to be 0.0040nA; the count rate is stabilized at 2450cps; the acquisition area size is 80nm×80nm. The collected EDS data is quantitatively analyzed (using the non-standard sample method for quantification), and the results show that the Hf content of 1 straight interface is 0.14%, which is classified as strong segregation interface; the Hf content of 1 curved interface is 0.07%, which is classified as weak segregation interface.

[0030] (4) Data processing and error analysis The EDS data of the 2 interfaces are divided into a 10x10 quadrat grid, that is, each interface data contains 100 pixel points, 10 quadrats containing interfaces are extracted as statistical samples (n=10), and the EDS analysis software is used to obtain the following: Weak segregation interface P element mass percentage (wt%): 0.05, 0.08, 0.07, 0.06, 0.08, 0.07, 0.09, 0.06, 0.08, 0.07; The average value of the element mass percentage (wt%) is calculated: ; The standard deviation of the sample (indicating the degree of data dispersion) is calculated (wt%): ; The standard error of the average value of the weak segregation interface element mass percentage (wt%) is calculated: ; The expanded uncertainty of the mean value at a 95% confidence level (i.e., the half-width of the confidence interval) is calculated: ; The average value of the final weak segregation interface element mass percentage and the 95% confidence level are: ; Strong segregation interface P element content (wt%): 0.12, 0.13, 0.15, 0.14, 0.16, 0.17, 0.12, 0.18, 0.14, 0.15; The average value of the element mass percentage (wt%) is calculated: ; The standard deviation of the sample (indicating the degree of data dispersion) is calculated: ; The standard error of the average value of the strong segregation interface element mass percentage (wt%) is calculated: ; The expanded uncertainty of the mean value at a 95% level (i.e., the half-width of the confidence interval) is calculated: ; The average value of the final strong segregation interface element mass percentage and the 95% confidence level are: ; The weak segregation number interface accounts for x=4 / 6≈66.7%; the strong segregation number interface accounts for y=2 / 6≈33.3%; The final mass percentage of P element (wt%) is calculated by the formula of the application: ; The result was compared with the overall Hf content of 0.10% wt% measured by inductively coupled plasma mass spectrometry (ICP-MS), and the result confirmed that it was consistent with the chemical composition of 0.10% wt%. Based on the judgment criteria of this invention, the reliability of the measured wt% result was confirmed.

[0031] Comparative Example 1 The same sample area as in Example 1 was used, but only one curved interface was randomly selected for 25 minutes of EDS surface scanning data acquisition.

[0032] The EDS data of this single interface was also divided into 10×10 quadrats, and 10 quadrats containing the interface were extracted as statistical samples to obtain the P element content (wt%): 0.18, 0.17, 0.18, 0.19, 0.17, 0.18, 0.18, 0.17, 0.18, 0.19; Calculate the average elemental mass percentage (wt%): ; Calculate the sample standard deviation (indicating the degree of data dispersion) (wt%): ; The standard error (wt%) of the average mass percentage of elements at strong segregation interfaces is calculated as follows: ; Calculate the expanded uncertainty of the mean at a 95% confidence level (i.e., the half-width of the confidence interval): ; The final average mass percentage of weakly segregating interface elements and its 95% confidence level: ; This result deviates significantly from the average value of the P content (wt%) of strongly segregating interfaces calculated by statistically analyzing multiple interfaces in Example 1 (approximately 23.5%), and the uncertainty intervals overlap to a limited extent. This demonstrates that a lack of statistical representativeness of multiple interface types leads to inaccurate conclusions, highlighting the necessity of interface morphology statistics and classification collection in step c) of this invention.

[0033] Comparative Example 2 EDS surface scanning data was acquired in the same area as in Example 1 for only 5 minutes, with other parameters remaining unchanged. Due to the significantly shortened acquisition time, the count was severely insufficient and the signal-to-noise ratio was poor. Ten quadrats containing the interface were extracted from the same group of weakly segregating interfaces as statistical samples, and the P element content (wt%) was obtained as follows: 0.04, 0.11, 0.02, 0.08, 0.13, 0.06, 0.10, 0.01, 0.12, 0.05.

[0034] The average value of the mass percentage of the element is 0.072, but the sample standard deviation is as high as 0.038, the expanded uncertainty of the average value at a 95% confidence level is 0.027, and the final result is 0.072 ± 0.027 (wt%), and the uncertainty range is as high as 37.5% of the average value. This is in sharp contrast to the stable results obtained after a long time of 25 minutes in Example 1 (0.079 ± 0.011, with an uncertainty range of 13.9%), which proves that the collection time of 20-30 minutes specified in step c) of the present application is crucial for ensuring the statistical significance and low uncertainty of micro-trace element analysis.

[0035] Comparative Example 3 The sample with a thickness of 180 nm was analyzed, and other parameters were the same as in Example 1. Due to serious electron beam multiple scattering, the spatial resolution decreased significantly, and EDS analysis was performed on the same strong segregation interface, and the P element content (wt%) was obtained: 0.19, 0.22, 0.25, 0.20, 0.24, 0.18, 0.17, 0.26, 0.16, 0.21. The average value of the mass percentage of the element (wt%) was 0.210, which was much higher than the result of the corresponding interface of the 70 nm thin zone sample in Example 1 (0.136). This result is systematically significantly higher (about 54% deviation), and the sample standard deviation (wt%) is 0.033, and the expanded uncertainty of the average value at a 95% confidence level (wt%) is 0.023, and the uncertainty range is as high as 109.5% of the average value. It is proved that the thickness of the sample <100 nm is a necessary condition to ensure the quantitative accuracy and avoid the introduction of systematic errors by matrix effect.

[0036] The above only describes the preferred embodiments of the present application and is not intended to limit the protection scope of the present application. Any equivalent changes or modifications made in accordance with the spirit and essence of the present application should be covered within the protection scope of the present application.

Claims

1. A method for quantitative analysis of interfacial micro- trace elements of high temperature alloys by STEM-EDS, characterized in that, The method comprises the following steps: a) preparing a transmission electron microscope sample and controlling the thin area thickness of the sample to be less than 100 nm; b) using a field emission transmission electron microscope or a transmission electron microscope equipped with a spherical aberration corrector to perform STEM imaging at an acceleration voltage of 200 kV-300 kV, adjusting the beam spot size to 5-7, aligning the optical path, and optimizing the collection angle, energy resolution and detection efficiency of the EDS probe to meet the detection accuracy requirements of micro trace element analysis; c) at low magnification 2000 - 3000 Next, the interfaces with different characteristic morphologies were counted by high-angle annular dark-field imaging, and the proportion of each type of interface was recorded. When the normal direction of the interface along the length direction Δθ ≥ 10°, it was marked as a curved interface; otherwise, it was marked as a straight interface. Subsequently, at high magnification 200k - 300k Next, a representative interface was selected from each type of interface for EDS area scan data collection for 20-30 minutes. During the collection process, the electron beam drift correction function was enabled, and the probe current was controlled to be ≤ 0.0040 nA, and the count rate was ≥ 1 kcps. d) defining the interface with an element content of 0-0.1wt% and not containing 0.1wt% as a weak segregation interface, and defining the interface with an element mass content of 0.1%-1% as a strong segregation interface according to the EDS data obtained in step c); e) The EDS data results of each type of interface collected in step c) are respectively divided into n x n quadrats, and the element mass percentage a1, a2…a of weakly segregated interfaces and the element mass percentage b1, b2…b of strongly segregated interfaces are respectively obtained by selecting n quadrats containing interfaces n and n The number of weakly segregated interfaces accounts for x, and the number of strongly segregated interfaces accounts for y. f) performing average processing on the obtained element content data to obtain the average mass percentage of the elements in the strong segregation interface and the weak segregation interface, respectively: ; ; wherein, is the average mass percent content of the element at the weakly segregated interfaces; is the average mass percent content of the element at the weakly segregated interfaces; is the average mass percent content of the element at the weakly segregated interfaces; is the average mass percent content of the element at the weakly segregated interfaces; Statistical analysis is performed on the obtained element content data, and the sample standard deviation is calculated to represent the dispersion degree: ; ; wherein Ss is the sample standard deviation of the mass percent of weakly segregated interfacial element, Ss is the sample standard deviation of the mass percent of strongly segregated interfacial element; The A-class standard uncertainty of the element content at the interface is estimated by the mean standard error: ; ; wherein is the standard deviation of the average value of the mass percentage of weakly segregated interfacial elements; is the standard deviation of the average value of the mass percentage of strongly segregated interfacial elements; According to the selected 95% confidence level, the degrees of freedom are found to be of distribution critical values , the expanded uncertainty of the average of the strongly and weakly segregated interface element content is calculated: ; ; wherein, and represents the expanded uncertainty of the mean at the 95% confidence level, which is half the width of the confidence interval; The average value of the element mass fraction at the weak segregation interface and its 95% confidence level are: ; The average value of the element mass fraction at the strong segregation interface and its 95% confidence level are: ; g) using the formula to calculate the final mass percent content of the target element ; Wherein, x is the proportion of the number of weak segregation interfaces; y is the proportion of the number of strong segregation interfaces.

2. The method for quantitative analysis of trace elements in the interface of superalloy by STEM-EDS according to claim 1, characterized in that, In step a), the transmission electron microscope sample is prepared by electrolytic polishing or focused ion beam method, and the thin area thickness of the sample is controlled in the range of 50 nm to 100 nm.

3. The method for quantitative analysis of trace elements in the interface of superalloy by STEM-EDS according to claim 1, characterized in that, In step c), the interfaces with different characteristic morphologies include straight line interfaces and curved line interfaces, wherein when the normal direction Δθ of the interface along the length direction is ≥10°, it can be marked as a curved line interface; otherwise, it is marked as a straight line interface.

4. The method of claim 1, wherein the micro-amount of element of the interface of the superalloy is quantitatively analyzed by STEM-EDS. In step b), the acceleration voltage of the transmission electron microscope is set to 200 kV.

5. The method for quantitative analysis of trace elements in the interface of superalloy by STEM-EDS according to claim 1, characterized in that, In step c), the high magnification is 250k .

6. The method of claim 1, wherein the micro-amount of element of the interface of the superalloy is quantitatively analyzed by STEM-EDS. In step c), the EDS face scanning data acquisition time is 25 minutes to 30 minutes.

7. The method of claim 1, wherein the micro-amount of element of the interface of the superalloy is quantitatively analyzed by STEM-EDS. After step g), step h) is further included: comparing the calculated target element mass percentage content interval wt% with the known chemical composition mass percentage wt0% of the element in the high-temperature alloy, when wt0% is located in the uncertainty interval of wt%, it is confirmed that the detection result wt% has reliability.

Citation Information

Patent Citations

  • Method for determining distribution state of trace elements in high-temperature alloy

    CN114137010A

  • Near-micron near-in-situ-multi-mode characterization method for trace elements of high-temperature alloy

    CN118483257A

  • Micro-area distribution detection method for micro and / or trace component elements in nickel-based single crystal superalloy

    CN120161080A

  • Quantitative analysis device for trace carbon and quantitative analysis method for trace carbon

    US20170336336A1

  • Element concentration measuring method and apparatus, and semiconductor device fabrication method and apparatus

    US6040198A